P9 HIF activator DMOG improves functional recovery following ischaemia-reperfusion in the type 2 diabetic heart. (26th October 2016) - Fialho, MdL Sousa; Thompson, HEC; Dodd, M; Ball, V; Carr, CA; Tyler, DJ; Heather, LC
Abstract : Type 2 diabetes results in abnormal cardiac metabolism, with an impaired ability to upregulate anaerobic glycolysis under stress. Diabetic hearts have decreased adaptation to hypoxia, further adding to the reliance on fatty acid oxidation for cardiac energy generation. We suggest activation of Hypoxia-Inducible Factor (HIF) may be beneficial for the type 2 diabetic heart, as it may promote glycolysis and improve function. The high-fat fed, low dose streptozotocin rat model of type 2 diabetes was used. The HIF activator, dimethyloxalylglycine (DMOG) was given i.p. (40 mg/kg) on three alternate days. Hearts from control and diabetic rats were perfused and subjected to low-flow (0.3 ml/min/gww) ischaemia and reperfusion, with metabolism and function measured throughout. Diabetic hearts showed decreased rate-pressure product following ischaemia-reperfusion, demonstrating a functional impairment. Diabetic hearts had decreased glycolysis, increased fatty acid oxidation rates, and increased myocardial triacylglycerol (TAG) concentrations. DMOG treatment resulted in faster recovery and improved function after reperfusion in diabetic hearts. However, glycolytic rates were not changed by DMOG. Instead, fatty acid oxidation rate was further increased during reperfusion in DMOG-treated diabetic hearts, as was cardiac TAG concentrations. Plasma TAG and non-esterified fatty acids were lowered with DMOG treatment in diabetic rats. Markers of fatty acid oxidation and HIF signalling were unchanged after reperfusion. Treatment with the HIF activator, DMOG, has functional benefits for the diabetic heart following ischaemia-reperfusion, despite no upregulation of glycolytic metabolism. Paradoxically, DMOG treatment promoted cardiac lipid metabolism and improved blood lipid profile in type 2 diabetes.